Phytoester profiling of the nut of spondias mombin - Uzoekwe, Ngozi Maureen; Odokwo, Edet Okon (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
The phytoester content of the nut of Spondias mombin has been carried out. The nut of Spondias mombin was crushed and macerated in n-hexane at room temperature. The n-hexane extract was concentrated under a vacuum and then profiled for the presence of phytoesters using the gas chromatography-mass spectrometry, GC-MS instrumentation method of analysis. Six phytoesters were identified with tetradecanoic acid, 12-methyl-, methyl ester,(S)- (41%) as the major candidate while acetic acid, fluoro ethyl ester (9%) and butanoic acid, methyl ester (9%) as the minor candidates respectively. The present study has established the presence of phytoesters in the nut of Spondias mombin.